1959
DOI: 10.1071/bi9590524
|View full text |Cite
|
Sign up to set email alerts
|

Variation and Dominance at the Scute Locus in Drosophila Melanogaster

Abstract: SummaryA genotypic scale, which is additive, has been worked out for variation of scutellar bristle number in D. melamoqaster, sc+ is shown to be partially dominant to scs», the first substitution of SC SC for sc+ having about six times more effect on genotypic value than the second. Canalization at four bristles is responsible for complete dominance of sc+ in stocks whose mean genotypic value gives a mean phenotype of four bristles in sc+ flies. A function converting the phenotypic to the genotypic scale is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1960
1960
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…In other words, selection for the typical quantitative character was more likely to change the degree of dominance for the correlated but canalized character than that for the selected character. This contrasting difference between the two characters is in accordance with the view that dominance becomes complete due to developmental canalization (Rendel 1959;cf. Waddington 1957).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In other words, selection for the typical quantitative character was more likely to change the degree of dominance for the correlated but canalized character than that for the selected character. This contrasting difference between the two characters is in accordance with the view that dominance becomes complete due to developmental canalization (Rendel 1959;cf. Waddington 1957).…”
Section: Discussionsupporting
confidence: 67%
“…Rendel (1959) observed that a difference in scutellar bristle number between the heterozygote and the sc+ homozygote was expressed when the influence of canalization was partly reduced by selection, and attributed the high degree of dominance to the canalization at four bristles of the wild type. A similar proposition that developmental canalization of the wild type results in dominance or that dominance is a form of canalization has been long expounded (Muller 1932;Plunkett 1932;Waddington 1957), but theoretical development and experimentation came about much later (Rendel 1967).…”
Section: Introductionmentioning
confidence: 98%
“…The mutant or selection merely moved the population to different parts of the one sigmoid curve of relationship between genotype and phenotype. Rendel (1959bRendel ( , 1962 maintained the same position in subsequent studies but in a later paper (RendeI1963) allowed doubts about its validity when sc flies in a high line showed a lower degree of canalization at 4 bristles than sc+ flies normally do. Dun and Fraser (1959), in their similar experiments with tabby (Ta) mice, preferred the view that the mutant directly disrupts the canalizing genotype and that selection response followed different dose-response curves for the different genotypes.…”
Section: Discussionmentioning
confidence: 98%
“…For if the mean of the distribution falls near the 0 or 4 class large portions of it will lie beyond these thresholds, and there will be no information about such portions since the 0 and 4 class boundaries are the most extreme crossed by either selection line. The method and justification of the analysis are dealt with in greater detail by Rendel (1959b).…”
Section: Experimental Prooedurementioning
confidence: 99%
“…Canalization describes the tendency of a developmental process to hold to its normal course in the face of both genetic and environmental forces tending to deflect it into other channels. The existence of canalization in the development of the scutellar bristles of Dro8ophila melanogaster has been demonstrated by Rendel (1959aRendel ( , 1959b. The presence of the 8C se gene segregating in a set of selection lines reduced the number of bristles to about one in scute males and two in scute females.…”
mentioning
confidence: 99%